Battery thermal management systems based on nanofluids for electric vehicles. (June 2022) - Abdelkareem, Mohammad Ali; Maghrabie, Hussein M.; Abo-Khalil, Ahmed G.; Adhari, Ohood Hameed Kadhim; Sayed, Enas Taha; Radwan, Ali; Elsaid, Khaled; Wilberforce, Tabbi; Olabi, A.G.
Abstract: The continuous rapid growth of the world population over the coming decade remains a crucial issue that requires ambitious innovations such as electric vehicles (EVs) to decarbonize the transportation sector. Temperature sensitivity is a critical issue in lithium-ion batteries (LIBs) for EVs. The control of the working temperature lithium-ion battery is critical to its performance and long-term durability. Battery thermal management systems (BTMSs) are based on different cooling methods using air, liquid, phase change materials, heat pipe, etc. A review of different sorts of cooling strategies utilized in battery pack thermal management with a focus of those based on nanofluid is presented in the current paper. Additionally, the utilization of nanofluids combined with phase change materials (PCMs) and heat pipes (HPs) for BTMSs is also introduced. Nanofluids are effectively utilized to improve the thermal management of the batteries. Hybrid cooling system based on nanofluids for BTMSs decreases the temperature rise and consequently improves the temperature uniformity in comparison with the single BTMS. Finally, this current review describes that more works concerned with BTMS are still indispensable to enhance the technology and advancements of EVs. Highlights: Characteristics and performance of battery thermal management systems are studied. Enhanced thermal management systems based on nanofluids is investigated. Number of hybrid thermal management systems combined with nanofluids are introduced. Challenges and development of BTMSs are proposed.